2020
DOI: 10.1093/ejcts/ezaa079
|View full text |Cite
|
Sign up to set email alerts
|

A structured approach to native mitral valve infective endocarditis: Is repair better than replacement?

Abstract: OBJECTIVES Mitral valve repair in native active infective endocarditis is technically challenging. The survival benefit over valve replacement is poorly established and possibly absent because of the high risk of repair failure and reoperation. In this study, we explore the results of our structured approach in these patients. METHODS Between January 2000 and January 2017, 149 patients underwent surgery for native mitral infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 16 publications
5
25
0
Order By: Relevance
“…The repair rate in our study was similar to that reported in the review of Feringa et al, but clearly lower than the feasibility reported by Defauw et al of 66% [21] or by de Kerchove et al of 80% [22]; on the other hand, we registered a lower in-hospital mortality (4%) than the latter two, who reported 15.4% and 16%, respectively. We favored safety, at the price of a lower rate of complex repair procedures, with similar long-term survival rate.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The repair rate in our study was similar to that reported in the review of Feringa et al, but clearly lower than the feasibility reported by Defauw et al of 66% [21] or by de Kerchove et al of 80% [22]; on the other hand, we registered a lower in-hospital mortality (4%) than the latter two, who reported 15.4% and 16%, respectively. We favored safety, at the price of a lower rate of complex repair procedures, with similar long-term survival rate.…”
Section: Discussionsupporting
confidence: 86%
“…Similar to the degenerative MR experience, valve repair recently became the procedure of choice in IE, as confirmed by several studies [18][19][20][21][22]. Patients who undergo mitral valve repair need significantly fewer reinterventions during the early post-operative period and long-term follow-up and have less long-term IE relapses and cerebrovascular events.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Acute severe regurgitations which lead to heart failure should be managed by surgical intervention as soon as possible [ 11 ]. In patients with active infective endocarditis, valve repair seems to be a better option than replacement [ 12 ] as valve replacement is associated with the risk of future episodes of endocarditis [ 13 ]. However, our patient was not in active infection and underwent both mitral and aortic valves replacement.…”
Section: Discussionmentioning
confidence: 99%